HUBUNGAN LINGKUNGAN TERHADAP IMPLEMENTASI KEBIJAKAN KAWASAN TANPA ROKOK DI SMA RAKSANA MEDAN TAHUN 2018 - Florenly, Florenly - (Program Studi Kesehatan Masyarakat Universitas Sari Mutiara Indonesia, 2018)
Smoking is one of the addictive substances that when used cause harm to the health of individuals. Indonesia is the third country with the largest number of smokers in the world after China and India. The increase in cigarette consumption has an impact on the higher burden of diseases caused by smoking and the increase in the death rate from smoking. One effort to reduce exposure to cigarette smoke, Medan City Government issued a Regional Regulation of Medan City Number 3 of 2014 concerning Non-Smoking Areas. The research problem is how the Analysis of the Effect of Communication,Attitudes and Environment on the Implementation of Non-Smoking Area Policy in Raksana High School Medan. This study aims to determine the implementation of the Non-Smoking Area Policy at the school. The purpose of this study is how to analyze the relationship of communication, attitudes and environment towards the implementation of the No Smoking Area policy in Raksana Medan High School in 2018. This type of research is a cross-sectional survey with an explanatory research method approach. The research data was obtained from the results of giving questionnaires and documentation. Data analysis using SPSS data analysis.The research used cross-sectional survey with an explanatory research method approach method. The data were gathered by conducting questionnaire, observation, and documentation and analyzed by using interactive data analysis by SPSS. The results showed a significant relationship between the influence of communication on the implementation of non-smokeless regional policies in SMA Raksana Medan with p value = 0.01,there was a significant relationship between the influence of attitudes towards the implementation of non-smokeless area policy in SMA Raksana Medan with p value = 0.02 and there is a significant relationship between the influence of the environment on the implementation of non-smoking area policy in SMA Raksana Medan with p value = 0.001. So that the Implementation of the No Smoking Area Policy in SMA Raksana Medan has not run optimally. The conclusion was that the implementation of the policy on KTR would not run well if there were some obstacles such as communication,attitude and environment. It is recommended that personnel and budget be added, socialization medium be provided through promotion video and health promotion regularly about KTR and strict sanction.  Keywords : Communication, Attitude, Environment, Policy, No Smoking Area